2007
DOI: 10.1002/ca.20508
|View full text |Cite
|
Sign up to set email alerts
|

Bony landmarks as an aid for intraoperative facial nerve identification

Abstract: DeceasedIdentification of the facial nerve trunk is essential during surgery of the parotid gland. Numerous landmarks have been researched and used. The relation between the facial nerve to two constant bony landmarks, the tip of the mastoid process and the central point of the transverse process of the atlas was investigated. Forty cadavers were dissected. A preauricular incision exposed the nerve trunk. Bony landmarks were identified and marked. The distance from the nerve trunk to the mastoid process and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…8 Greyling et al found the distance as 0.91 AE 0.20 cm on the left side and 0.93 AE 0.16 cm on the right side. 9 Our values (1.60-cm right side and 1.57-cm left side) were different from their values as they have done the study on the dissected cadaver and we have done it directly on the bone.…”
Section: Discussionmentioning
confidence: 67%
“…8 Greyling et al found the distance as 0.91 AE 0.20 cm on the left side and 0.93 AE 0.16 cm on the right side. 9 Our values (1.60-cm right side and 1.57-cm left side) were different from their values as they have done the study on the dissected cadaver and we have done it directly on the bone.…”
Section: Discussionmentioning
confidence: 67%
“…Greyling et al [10] demonstrated that the mean distance between the mastoid process and facial nerve for the left was 9.18 ± 2.05 mm and for the right, 9.35 ± 1.67 mm on cadaver dissection.…”
Section: Discussionmentioning
confidence: 99%
“…15 Bony landmarks to identify the facial nerve were proposed in another cadaveric study. 16 The usefulness of these approaches in live surgery has not been tested.…”
Section: Discussionmentioning
confidence: 99%